Corpos em transição: análise do corpo transexual na penitenciária Desembargador Flósculo da Nóbrega - Costa, Wendel Araújo da (2024)
This dissertation has as its main objective the focus on the experience of transgender women who live in the Desembargador Flósculo da Nóbrega Penitentiary, situated in the city of João Pessoa – PB, and their transgender process and other changes which may occur in prison situation. The selected penitentiary popularly named Prison of Roger, in respect to its municipal location, was the first in Brazil to institute a specific sector for the LGBT population. In the state of Paraíba, there are public politics concerned with the transgender process for which one wants to start, but this procedure is not assured for those in prison situation. The research was carried out using ethnographic techniques to obtain data in the field, which helped in the understanding of the transgender’s experience in prison. The general objective of this study is to analyze the process of obtaining hormonotherapy for transgender inmates, having in view the guarantee established in law. As specific objectives, this study tried to identify the public political programs present in Desembargador Flósculo da Nóbrega Penitentiary, considering the healthcare program of the institution, to observe, the custody’s point of view, the application of assumptions State’s guarantee and also to investigate the impact of prison on transgender bodies having as start the obtained testimonies. It was demonstrated that, despite progress in this scenario and the offering of a healthcare plan, the omission promotes physical and emotional impacts on transgender inmates.